1998
DOI: 10.1089/dna.1998.17.957
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the 5′ Promoter Region of the Rat Lamin A Gene

Abstract: The A-type lamins are constituents of the nuclear lamina in differentiated cells and have been proposed to play an important role in nuclear organization. In this study, we isolated and characterized a genomic clone containing the putative promoter region of the rat lamin A gene. Sequence analysis of about 2 kb of this region combined with primer extension data revealed the presence of a TATA box at -33, a GC box at -101, and AP1 motifs at -7, -424, and -1677. Deletion analysis of the promoter fragments in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…These findings suggested that the LMNA promoter might be active in all cells and that distinct regulatory elements serve to silence LMNA expression in undifferentiated cells. Later, Tiwari et al [51] showed that AP1 and SP1 sites in the 5′ promoter of rat Lmna are sufficient for the active transcription, and suggested that conformational changes in chromatin might underlie cell-type specific repression of Lmna expression.…”
Section: Regulation Of the A-type Laminsmentioning
confidence: 99%
“…These findings suggested that the LMNA promoter might be active in all cells and that distinct regulatory elements serve to silence LMNA expression in undifferentiated cells. Later, Tiwari et al [51] showed that AP1 and SP1 sites in the 5′ promoter of rat Lmna are sufficient for the active transcription, and suggested that conformational changes in chromatin might underlie cell-type specific repression of Lmna expression.…”
Section: Regulation Of the A-type Laminsmentioning
confidence: 99%
“…These results suggest that cJun causes morphological transformation through direct or indirect transcriptional regulation of multiple genes related to the cytoskeleton and cell adhesion. The cytoskeletaland adhesion-related genes with the exception of collagen alpha 1 type 1 (Noti et al, 1996), annexin II (Braselmann et al, 1992), lamin A (Tiwari et al, 1998) and integrin alpha (also named p150 and CD11c) Lopez-Rodriguez et al, 1996;Noti et al, 1996), galectin 3 (Gaudin et al, 1997), and annexin I (Solito et al, 1998) represent novel targets of AP-1. These genes may cooperatively contribute to the observed morphological phenotypes by cJun.…”
Section: Identification Of Cjun-responsive Genesmentioning
confidence: 99%
“…Transfections of reporter plasmids and a b-galactosidase expression vector (pCH110 for NIH 3T3 and PCC-4 cells and pCMVSPORT bgal for CRL-1600 cells) were carried out as described [15,17]. Cells were lysed and aliquots were assayed for LUC activity using a kit from Promega Corporation (Madison, Wisconsin) and for b-galactosidase activity as described [21].…”
Section: Cell Culture and Dna Transfectionsmentioning
confidence: 99%